THE EFFECTIVENESS OF INQUIRY BASED LEARNING STRATEGY ON STUDENTS’ WRITING SKILL IN NARRATIVE TEXT - Sholihatul Hamidah Daulay; Yani Lubis Lubis; Nurhaliza Nurhaliza (Universitas Negeri Islam Sumatera Utara, 2023)
Today's senior high school pupils have difficulty learning to write. Students are expected to be able to express a variety of meanings (interpersonal, conceptual, textual) in interactional oral texts and monologue. Some researchers have demonstrated that using an effective strategy is one of the ways to solve problems; inquiry-based learning is one such strategy. This study aims to determine the significance of the effect of inquiry-based learning on students' narrative writing ability in tenth grade senior high school. Using a quasi-experimental design, thirty-one students in grade X-I and thirty-one students in grade X-II were studied. Using the purposive sample method, the experimental class X-I and the control class X-II were selected. The experimental class was taught using an inquiry-based learning strategy, while the control class was taught without such a strategy. In this investigation, essay tests were used for data collection. The examinations were administered before (pre-test) and after (post-test) the treatment. The result indicates that tobserve = 2,557, while ttable indicates 1,671 with df = 60 and a significance level of 0.05. Consequently, this Ha is approved while the H0 is rejected. In conclusion, inquiry-based learning is an effective strategy for the teaching and learning process because it allows students to engage in discussion to produce their finest writing product.Keywords: Inquiry-based learning, Narrative text, Teaching and learning Strategy, Writing skill